Promoting and Protecting Mental Health: A Delphi Consensus Study for Actionable Public Mental Health Messages. Issue 8 (November 2021) - Breedvelt, Josefien J. F.; Yap, Jade; Eising, Dorien D.; Ebert, David D.; Smit, Filip; Thorpe, Lucy; Kousoulis, Antonis A.
Purpose: Public health campaigns are still relatively rare in mental health. This paper aims to find consensus on the preventive self-management actions (i.e. "healthy behaviors") for common mental health problems (e.g. depression and anxiety) that should be recommended in mental health campaigns directed at the general public. Approach: A 3-round Delphi study Participants: 23 international experts in mental health and 1447 members of the public, most of whom had lived experience of mental health problems. Method: The modified Delphi study combined quantitative and qualitative data collection: 1) online qualitative survey data collection thematically analyzed, 2) recommendations rated for consensus, 3) consensus items rated by public panel on a Likert scale. Results: Expert consensus was reached on 15 behaviors that individuals can engage in to sustain mental health. Eight were rated as appropriate by more than half (50%) of the public panel, including: avoiding illicit drugs (80%, n = 1154), reducing debt (72%, n = 1043), improving sleep (69%, n = 1000), regulating mood (65%, n = 941), having things to look forward to (60%, n = 869). Conclusions: A series of healthy behaviors for the promotion and protection of mental health received expert and public consensus. To our knowledge, this is the first study to offer a set of actions for public health messaging for the prevention of poor mental health. Future research should focus on evaluating effectiveness of these actions in a universal primary prevention context.